Abnormalities of Cerebral White Matter Microstructure in Children With New-Onset, Untreated Idiopathic-Generalized Epilepsy - Long, Ran; Wang, Yuting; Chen, Lizhou; Deng, Dingmei; Mei, Lan; Mou, Jingping; Tang, Guangcai; Han, Fugang; Kemp, Graham John; Gong, Qiyong; Qiu, Lihua (Frontiers in Neurology, 2021)
Despite evidence for microstructural brain alterations in epilepsy patients, little is known about how these develop with age and the progress of the disease. The aim of this study was to investigate microstructural abnormalities of the white matter (WM) in children with new-onset, untreated idiopathic generalized epilepsy (IGE) using the MRI technique of diffusion tensor imaging (DTI). The study was approved by the institutional review board, and all individuals or their parents gave signed informed consent. In total, 45 IGE patients (age 5-18 years, male:female 26:19) and 32 healthy controls (age 5-18 years, male:female 21:11) were included. Voxel-based analysis was used to compare patients and controls, and Pearson correlation analysis to investigate relationships between altered DTI metrics and clinical parameters. Compared with controls, IGE patients showed increased mean diffusivity (MD) in the left splenium of the corpus callosum; increased fractional anisotropy (FA) in the right WM of the superior and middle frontal gyri; increased axial diffusivity (AD) in the WM of right corona radiata and left occipital lobe; and decreased AD in the WM of the left thalamus and the right middle cerebellar peduncle. There was no correlation between the altered diffusion parameters and clinical measures. Our study demonstrated several distinct microstructural impairments in children with new-onset, untreated IGE, of which altered AD might be the most sensitive marker of dysmyelination. The increased FA in the IGE group might suggest an initiating or compensatory mechanism that is activated prior to cognitive decline in these children. Key Points: 1. Microstructural abnormalities exist from the very beginning of IGE. 2. AD seems to be more sensitive to WM injury than other diffusivity parameters in children with new-onset IGE. 3. The increased FA in children with new-onset, untreated IGE may suggest a gradual progression of cognitive impairments and possible compensatory mechanisms of IGE prior to cognitive decline.